African Handbook of Climate Change Adaptation 2021
DOI: 10.1007/978-3-030-45106-6_227
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Adoption of Climate Smart Practices for Increased Productivity in Nigeria

Abstract: In a bid to reinforce the efforts of agricultural professionals within the domain of climate change studies and with particular emphasis on rural farmers in Nigeria, this chapter explores the mechanics for adoption of climate smart agricultural practices among rural farmers for an increased agricultural productivity. Climate-Smart Agriculture (CSA) is paramount to the success of farming activities today in the face of the menace of the impact of climate change. Climate Smart Agricultural Practice (CSAP) is one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…These findings are consistent with the [18] study conducted in sub-Saharan Africa and Ethiopia, which revealed that farmers perceived that adopting CSAPs could enhance climate change adaptation and resilience by improving soil fertility and reducing soil erosion. This also aligns with those of [19], which highlighted the positive effects of soil management, composting, and agroforestry on soil health.…”
Section: Discussionsupporting
confidence: 85%
“…These findings are consistent with the [18] study conducted in sub-Saharan Africa and Ethiopia, which revealed that farmers perceived that adopting CSAPs could enhance climate change adaptation and resilience by improving soil fertility and reducing soil erosion. This also aligns with those of [19], which highlighted the positive effects of soil management, composting, and agroforestry on soil health.…”
Section: Discussionsupporting
confidence: 85%
“…However, the use of green house and flood resistant crop varieties recorded the lowest level of awareness (Mean = 1.44). This result may not be surprising as reports from literature already suggested that farmers are highly vulnerable to climate change impact (Wisner, 2016;ICRISAT, 2019;Fawole and Aderinoye-Abdulwahab, 2021) and it also suggests a low level of knowledge of CSA-TIMPs especially. This finding is in consonance with that of Tiamiyu et al (2017) who found that large proportion of agricultural stakeholders were not aware of most CSA practices in Northern Nigeria and this has resulted in low uptake of the CSA practices in the region.…”
Section: Level Of Awareness Of Climate-smart Agriculture Technologies...mentioning
confidence: 78%
“…Haider (2019) also reported that farmers in the semi-arid region of Nguru, Nigeria mitigated the impact of climate variability by using adaptation strategies such as planting of different crop varieties, soil and water conservation, diversification into non-farm activities and use of irrigation among others. Similarly, it was found that most farmers in Adamawa are well aware of climate change and have been responding to its effect by planting improved and extreme weather tolerant crop varieties as well as planting of early maturing crop varieties (FAO and ICRISAT, 2019; Fawole and Aderinoye-Abdulwahab, 2021). Sofoluwe et al (2011) found that the farmers in Osun State perceived climate change through their experience of a surge in temperature and decrease in rainfall.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, the study examines the regressive influence of constraints on the practice of Climate-Smart Agriculture (CSA), shedding light on the factors hindering the adoption and implementation of CSAPs. However, the constraints to the implementation of CSA commonly filtered from the study by Obianefo et al (2019) [39] ; Kaptymer et al (2019) [26] ; Salisu (2022) [45] ; Fawole, and Aderinoye-Abdulwahab (2021) [17] ; Chukwu et al (2023) [14] include the high cost of improved varieties of yam, the high cost of farm labour, and lack of financial resources, poor access to information sources relevant to adaptation, lack of relevant information on adaptation measures, lack of access to weather forecasts and interpretation, lack of irrigation facilities, absence/weak implementation of government policies, scarcity and high cost of farm inputs, lack of drainage facilities, inadequate extension services, insecure land tenure system, and low management skills due to low literacy. An innovative aspect of this study lies in its methodological approach, which utilizes censored regression to understand the individual effects of CSAPs on food security dimensions, a methodology that has not been extensively applied in previous studies in Southeast Nigeria.…”
Section: Statement Of the Problemmentioning
confidence: 99%